Effect of mindfulness on exam anxiety among undergraduate dental students: A quasi-experimental study - Kadaramandalagi, Kavya Manjunath; R., Rekha; G., Radha (International Journal Of Community Medicine And Public Health, 2024)
Background: Exam anxiety is the primary factor preventing students from achieving their academic goals and is an unpleasant worry-based experience. Where in, Mindfulness helps to uphold consciousness, release oneself from a deeply held connection to ideas, emotions, or sensations, and cultivate a stronger sense of emotional equilibrium and wellbeing. Research indicates, mindfulness education intervention leads to significant reduction in anxiety levels. Hence, the present study aims to assess the effectiveness of mindfulness education intervention on anxiety among undergraduate students. Methods: A total of 130 Undergraduate students (3rd and 4th year) from the Vokkalighara Sangha Dental College was included in the study. A spielberger anxiety Test Scale (SATS) was used to assess the anxiety level. Mindfulness attention awareness scale (MAAS) was used to assess the stress among the participants Results: Descriptive statistics was performed to assess the frequencies of responses to the questionnaire items. Statistical analysis to find out the association between the effectiveness of mindfulness education intervention on anxiety. Comparison of change in mindfulness (MAAS) scores among study participants at baseline were 29.30±4.89 and after the intervention was 79.76±2.68 and self-evaluated anxiety (SATS) scores at baseline was 66.03±2.17 and after the intervention was 29.11±2.94, the mean difference in Anxiety scores and Mindfulness scores was statistically significant (p≤0.001) Conclusions: Mindfulness exercise reported significant improvement in overall well-being and effective strategy for promoting Students mental health, academic success and overall flourishing.